Kontribusi Nilai-Nilai Kebangsaan yang Bersumber dari UUD 1945 dan NKRI dalam Penerapan Kesehatan, Keamanan, dan Keselamatan Kerja (K3) dan Corporate Social Responsibility di PT Aqua Golden Mississippi - Indira Wardasyifa; Edy Soesanto; Sherlina Putri Aulia (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
PT Aqua Golden Mississippi Tbk has implemented an effective Occupational Safety and Health (OSH) program at all stages of production, distribution to consumers, and post-production activities, as regulated in the Occupational Safety Law No. 1 of 1970. This program requires companies to implement occupational safety and health measures in running their business. As a bottled mineral water company, PT Aqua Golden Mississippi fulfills OSH obligations and carries out Corporate Social Responsibility (CSR) programs in accordance with applicable regulations. The company's commitment to OSH not only creates a safe work environment but also strengthens a sense of social responsibility and nationalism by ensuring quality and safe products for the Indonesian people. The CSR program is related to national values ​​and independence in the context of the Unitary State of the Republic of Indonesia, by preserving living space and utilizing resources for the sustainability and welfare of society. As a legal entity, PT Aqua Golden Mississippi has social and environmental responsibilities in accordance with Government Regulation no. 47 of 2012, which aims to maintain company continuity and preserve the environment. This research uses a literature study method, where data is collected from articles, books and national scientific journals. The aim of this research is to understand how national values ​​in OSH are applied in the production process of PT Aqua Golden Mississippi and the company's contribution to society and the environment through CSR programs. The research results show that PT Aqua Golden Mississippi has successfully implemented K3 and CSR programs, fulfilling its obligations as a legal subject in accordance with the laws in force in Indonesia.